Transnational Filipina/o/x youth, intersectional identities, and school-community partnerships the gendered vulnerabilities of migration in Canada - Ticar, Jessica (Routledge Critical Studies in Gender and Sexuality in Education)
This book provides an in-depth examination of how Filipina mothers, serving as migrant caregivers, and their children navigate the experiences of family separation and reunification through Canada's Live-in/Caregiver Program (L/CP). It analyses how Filipina/o/x youth understand their political agency, the legacy of colonialism, and their sense of identity and belonging in urban schools through school-community partnerships. The work examines the global migration experiences of transnational Filipina/o/x youth and their mothers in nation-states such as Canada through the lens of the global domestic work industry. It connects the theoretical frameworks of critical and intersectional feminisms within a transnational context to the specificity of settler colonialism within Canada, a white settler nation-state. It underscores the pivotal role of school-community partnerships in facilitating the political agency of Filipina mothers and their children, and in shaping Filipina/o/x youths' transnational identities through equitable educational policies and, ultimately, im/migration policies and practices. This book is a valuable addition to the discourse on global migration, transnational feminism, and critical race studies in education. The book primarily targets scholars, researchers, graduate students in the fields of Gender Studies, Education, Psychology, Mental Health, Immigration/Transnational Studies, and Asian Canadian Studies. It is particularly relevant for those with specialist knowledge in Gender and Immigration Studies, as well as Equity and Social Justice Education, which includes a focus on supporting the participation of racialized im/migrants in the school system.